Dampak Volatilitas, Perspektif Return dan Preferensi Risiko Terhadap Keputusan Investasi Saham dan Cryptocurrency Pada Kalangan Milenial di Kota Palembang - Nisrinasari; Romli, Harsi; Tripermata, Lukita (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to analyze the impact of volatility, return perspective, and risk preferences on stock and cryptocurrency investment decisions among millennials in Palembang. Millennials tend to have a higher risk tolerance and interest in digital investments such as cryptocurrency. Using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method, the research findings indicate that volatility and risk preferences significantly influence investment decisions, especially in cryptocurrency, which exhibits high fluctuation levels. Return perspective also plays a crucial role in investment decision-making in both stocks and cryptocurrency.